2018
DOI: 10.1002/2017jd027934
|View full text |Cite
|
Sign up to set email alerts
|

Regional to Global Biogenic Isoprene Emission Responses to Changes in Vegetation From 2000 to 2015

Abstract: Isoprene, a dominant biogenic volatile organic compound that is mainly emitted by trees, has a significant impact on the atmospheric chemistry. Regional to global changes in biogenic isoprene emission associated with vegetation variations between 2000 and 2015 were estimated using the MEGAN model with satellite land cover data for inputs in this study. The satellite data estimates of land cover changes were compared to results from previous investigators that have either conducted regional studies or have used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 76 publications
7
47
0
Order By: Relevance
“…Based on ozone observations from 2013 to 2017, the North China Plain (NCP, an area about 400 000 km 2 in size, with Beijing located on its northeast edge; 35-42 • N, 112-119 • E), is identified as the area with the most severe ozone pollution in China compared to other regions such as the Yangtze River Delta and Pearl River Delta, possibly linked to the stimulation effect from enhanced hydroperoxy radicals (HO 2 ) due to a reduction in aerosol sink resulting from the decrease in PM 2.5 during this period (Li et al, 2019). Chen et al (2019) investigated the impact of meteorological factors such as temperature, wind speed and solar radiation on ozone pollution from 2006 to 2016 and noted that the severe ozone events in June 2017 around Beijing stand out and suggested a possible connection with the abnormal meteorological conditions. These studies motivated a need for a better understanding of the high-ozone problem over the NCP.…”
Section: Introductionmentioning
confidence: 99%
“…Based on ozone observations from 2013 to 2017, the North China Plain (NCP, an area about 400 000 km 2 in size, with Beijing located on its northeast edge; 35-42 • N, 112-119 • E), is identified as the area with the most severe ozone pollution in China compared to other regions such as the Yangtze River Delta and Pearl River Delta, possibly linked to the stimulation effect from enhanced hydroperoxy radicals (HO 2 ) due to a reduction in aerosol sink resulting from the decrease in PM 2.5 during this period (Li et al, 2019). Chen et al (2019) investigated the impact of meteorological factors such as temperature, wind speed and solar radiation on ozone pollution from 2006 to 2016 and noted that the severe ozone events in June 2017 around Beijing stand out and suggested a possible connection with the abnormal meteorological conditions. These studies motivated a need for a better understanding of the high-ozone problem over the NCP.…”
Section: Introductionmentioning
confidence: 99%
“…This effect possibly explains also the trend overestimation (by 0.4% per year) over the Southeastern United States. The trend underestimations over Southeast Europe (0.4% vs. 0.9% per year) and Western Russia (1% vs. 1.9% per year) likely reflect underestimated biogenic emissions (also suggested by the low bias of modeled columns over these regions, Figure ) and the impact of afforestation in Europe and Western Russia (Chen et al, ). The discrepancy over less productive and drier ecosystems such as Mexico and the Midwestern United States for both the trend (Figure ) and the correlation (Figure ) could be related to the neglect of soil moisture stress effect on the emission in the model.…”
Section: Resultsmentioning
confidence: 99%
“…Elsewhere, the modeled trends are comparatively smaller and in agreement with the observed trends when accounting for their respective uncertainties (Table ). The overestimations (by 0.4–0.7% per year) found over Amazonia and Borneo are possibly due to the combined effects of deforestation and increasing CO 2 on the emissions (Chen et al, ). The CO 2 effect alone is expected to cause a flux decline between −0.2 and −0.5% per year (section 2.3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They estimated the total emissions of BVOCs in China at 16.8 Tg in the mid‐2000s, which is an increase of 11.4% relative to the late 1980s, due to the combined effect of meteorology and land cover. A significant increase in the emissions of isoprene (>10%), the dominant BVOCs emitted in present‐climate state (Guenther et al, ), was found in central China during 2000–2015 with a large increase in tree coverage (~13%) because of extensive afforestation efforts (Chen et al, ). These results suggest that emissions of NMVOCs from China did not decrease after 2008.…”
Section: Discussionmentioning
confidence: 99%